An introduction to AI and criminal justice in Europe - Serena Quattrocolo (Revista Brasileira de Direito Processual Penal)
The article focuses on the need to start a comprehensive and multidisciplinary discussion about the specific interaction between AI and criminal justice, especially within the European context. Indeed, criminal law is considered, for several reasons, a realm in which computational modelling and AI cannot have a direct and relevant application. On the contrary, there is an urgent need to start a legal reflection about both the short- and long-term effects of such technology, that is reshaping all aspects of our social existence, justice included. The purpose of this article is to point out the most relevant risks in this scenario. There is no ambition to deliver answers but, rather, the need to set specific questions about if and how AI can be integrated into the criminal justice European systems. The author delays to a more comprehensive study any attempt of answering such questions.